Phylogenetic placement and new data on macro and micro morphology of Nopalxochia phyllanthoides (Cactaceae), an endangered species from Mexico - Martínez-González, César; Alcántara, Othón; Luna-Vega, Isolda; Garcia-Sandoval, Ricardo (Phytotaxa, 2015)
The phylogenetic placement of Nopalxochia phyllanthoides using DNA sequences of two plastid regions is investigated. New data on the micro- and macro-morphology are also presented. Detailed descriptions of habit, vegetative and reproductive structures, as well as micro-morphology of areoles, epidermic cells of the apical and medium part of the spines, stomata, pollen and seeds, are provided. The results obtained show the N. phyllanthoides is to be recognized as independent taxon, so correcting the previous treatment a taxon belonging to the genus Disocactus. A lectotype and epitype are designated for this species.